DO IBUPROFEN AND PHENOBARBITAL INFLUENCE DENGUE VECTOR TOLERANCE TO THE LARVICIDE TEMEFOS? - Morales-Rodríguez, Richar J. (2022)
The release of pharmaceutical products has increased in terrestrial and aquatic ecosystems, putting the biota at risk, being able to generate multiple impacts on organisms, from modifying enzymatic expression to intergenerational impact on exposed organisms. This study evaluated the influence of phenobarbital and ibuprofen on tolerance to the insecticide temephos in two populations of Aedes aegypti, La Esperanza (LE) and Rockefeller (Rock). Larvae I were exposed to 17.7 μg/ml ibuprofen and 200 μg/ml phenobarbital until reaching stage III; subsequently, larvae mortality to temephos (0.005, 0.025 and 0.050 μg/ml) and the enzymatic activity of esterases were determined. Phenobarbital was found to favors a higher tolerance to 0.025 μg/ml of temephos, at 24 hours of exposure, in the LE population (44.00 ± 6.93% mortality) as opposed to Rock (97.33 ± 2.67% mortality); furthermore, it decreased enzymatic activity of alpha esterases in Rock and LE specimens (0.3892 ± 0.0756 and 0.1722 ± 0.0194, optical density, respectively). Also, ibuprofen reports a lower LD90 (0.024 μg/ml temephos) than the control (DL90 = 0.039 μg/ml temephos) at 2 hours of exposure with temephos. It is concluded that phenobarbital increases the tolerance of Aedes aegypti larvae to temephos, and ibuprofen stimulates the activity of alpha- and beta-esterases.